2014
DOI: 10.1111/ijfs.12536
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flour storage and heat generated during milling on starch, dietary fibre and polyphenols in stoneground flours from two durum‐type wheats

Abstract: Summary In the perspective of cereal‐based functional food development, the research compared stone watermill and stone mill which differed in the heating generated during grinding (30 and 60 °C) and the effects of storage on the preservation of phytochemicals. After 6‐month storage of flour, a decrease in soluble dietary fibre (loss of 1.9–2.5 g 100 g−1) and bound polyphenols (loss of 6.2–8.5%) was observed, while other wheat grain components remained unvaried. Comparing the milling techniques, stoneground wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…KAMUT V R wheat could be a special raw material for improving the prebiotic properties of wheat-based products. Although the content of soluble dietary fiber was found lower in KAMUT V R flour than in grains of Triticum polonicum (average of nine spring lines) (Wiwart et al 2013), it was higher than in the Italian modern durum wheat variety Claudio (Di Silvestro et al 2014). In addition, KAMUT V R fibers have been shown to have a prebiotic effect and to promote the growth of Lactobacillus and Bifidobacterium (Marotti et al 2012).…”
Section: Technological and Nutritional Aspectsmentioning
confidence: 87%
“…KAMUT V R wheat could be a special raw material for improving the prebiotic properties of wheat-based products. Although the content of soluble dietary fiber was found lower in KAMUT V R flour than in grains of Triticum polonicum (average of nine spring lines) (Wiwart et al 2013), it was higher than in the Italian modern durum wheat variety Claudio (Di Silvestro et al 2014). In addition, KAMUT V R fibers have been shown to have a prebiotic effect and to promote the growth of Lactobacillus and Bifidobacterium (Marotti et al 2012).…”
Section: Technological and Nutritional Aspectsmentioning
confidence: 87%
“…Previous reports using different in vivo digestion methods showed that the interaction between stevia and other food components has the potential to influence postprandial glucose and insulin levels in humans (Alizadeh et al, 2014;Anton et al, 2010;Di Silvestro et al, 2014). However, none of the studies assessed the mechanism by which stevia was related to the release of reducing sugar during in vitro digestion and, thus, the glycaemic response in muffin products.…”
Section: In Vitro Predictive Glycaemic Responsementioning
confidence: 99%
“…Di Silvestro et al compared two different milling processes: stone mill and stone watermill, which varied in the milling temperatures (30 and 60°C). Stoneground grains (60°C) exerted the greatest resistant starch and amylose contents, which might be beneficial for a reduction of the GI.…”
Section: Gi Of Breadmentioning
confidence: 99%